2008
DOI: 10.1515/cclm.2008.126
|View full text |Cite
|
Sign up to set email alerts
|

Alternative antibody for the detection of CA19-9 antigen: a European multicenter study for the evaluation of the analytical and clinical performance of the Access® GI Monitor assay on the UniCel® DxI 800 Immunoassay System

Abstract: Background: Gastrointestinal cancer antigen CA19-9 is known as a valuable marker for the management of patients with pancreatic cancer. Methods: The analytical and clinical performance of the Access ᮋ GI Monitor assay (Beckman Coulter) was evaluated on the UniCel ᮋ DxI 800 Immunoassay System at five different European sites and compared with a reference method, defined as CA19-9 on the Elecsys System (Roche Diagnostics). Results: Total imprecision (%CV) of the GI Monitor ranged between 3.4% and 7.7%, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…We showed that in pancreatic and gallbladder cancer, best diagnostic power was achieved by CA19-9, with an AUC of 0.85 and a sensitivity of 60.6% at a 95% specificity versus benign gastrointestinal diseases. These results are in line with earlier study on pancreatic cancer that described AUCs of 0.827 (sensitivity of 53.2% at 95% specificity) and 0.850 (sensitivity of 58.1% at 95% specificity) when comparing them with benign gastrointestinal diseases using the Access™ GI Monitor and the Elecsys™ CA19-9 (22). In colorectal cancer, best performance was achieved by CEA with an AUC of 0.84 and a sensitivity of 51.7% at 95% specificity versus benign gastrointestinal diseases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that in pancreatic and gallbladder cancer, best diagnostic power was achieved by CA19-9, with an AUC of 0.85 and a sensitivity of 60.6% at a 95% specificity versus benign gastrointestinal diseases. These results are in line with earlier study on pancreatic cancer that described AUCs of 0.827 (sensitivity of 53.2% at 95% specificity) and 0.850 (sensitivity of 58.1% at 95% specificity) when comparing them with benign gastrointestinal diseases using the Access™ GI Monitor and the Elecsys™ CA19-9 (22). In colorectal cancer, best performance was achieved by CEA with an AUC of 0.84 and a sensitivity of 51.7% at 95% specificity versus benign gastrointestinal diseases.…”
Section: Discussionsupporting
confidence: 92%
“…For cardiac troponin I, an acceptable analytical performance of the LOCI™ method on the Dimension EXL (Siemens Healthcare Diagnostics) was found (21). The evaluation of the analytical performance of CA19-9 using non LOCI™-based immunoassays revealed minimal differences in slopes and intercepts when comparing two different immunoassays; good correlation was shown for all patients in their collective (22). In addition, for CA15-3 the analytical performance was accurate but not optimal and a difference in slope of 20-40% lower concentrations for the applied method was detected (23).…”
Section: Discussionmentioning
confidence: 98%
“…Of note, all CA 19-9 measurements in this study were conducted with the use of one defined assay (Elecsys), thus ruling out an assay-dependent analytic bias (8,21). In addition, we did not categorize CA 19-9, but modeled CA 19-9 as a continuous covariate where we found the logarithmic transformation of CA 19-9 as an adequate one to model the nonlinear relationship between CA 19-9 and the corresponding hazard.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Lastly, correlations of the biomarker development in the course of specific cancer therapies with the therapeutic outcome and=or disease progression are important points to consider in clinical marker validation before introduction of a new method into clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this comparison reveals the higher value scatter in the lower measuring range that is often observed in method comparison studies. [17][18][19] Possibly, this can be attributed to different antibody affinities resulting in discrepant values particularly when small amounts of antigens are present. Other studies compared each Vista marker with different methods and only over the entire measurement range.…”
Section: Discussionmentioning
confidence: 99%